Factors that Affect Intellectual Capital in Construction Companies - Koksal, Almula; Ercan, Tugce (HONG KONG POLYTECHNIC UNIV, 2008)
The purpose of this study is to investigate the effective intellectual capital measurement parameters for the construction companies and predicting the tendencies or the balance between the three main intellectual capital factors which create market value for the companies. In this research the intellectual capital of a construction company is considered, as by the Value Platform Model, to be composed of three main factors. These are: human capital, structural capital, and customer capital; 23 parameters that describe the human capital factor, 13 parameters for structural capital and 13 parameters for customer capital were identified after an extensive review of the management science literature. A survey tool was developed using these parameters and was administered to 25 large and medium size Turkish construction companies. The findings indicated that H19: education/experience level of senior management (mu=4,52), S16: improvement in the quality of project scheduling (mu=4,48), and C10:company's positive reputation on doing business (mu=4,64) were the leading parameters in human capital, structural capital and customer capital, respectively. This study also showed that human capital, structural capital, and customer capital have equal significance in construction companies. A conceptual framework was created for the Intellectual Capital (IC) tool of a construction company which is essential before the strategic IC management model has been executed.
Keywords: Intellectual capital; construction company; intellectual capital measurement models; knowledge economy; Business & Economics; Public Administration